2001
DOI: 10.1093/protein/14.9.699
|View full text |Cite
|
Sign up to set email alerts
|

Expression and stabilization of galactose oxidase in Escherichia coli by directed evolution

Abstract: We have used directed evolution methods to express a fungal enzyme, galactose oxidase (GOase), in functional form in Escherichia coli. The evolved enzymes retain the activity and substrate specificity of the native fungal oxidase, but are more thermostable, are expressed at a much higher level (up to 10.8 mg/l of purified GOase), and have reduced negative charge compared to wild type, all properties which are expected to facilitate applications and further evolution of the enzyme. Spectroscopic characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 31 publications
6
128
1
4
Order By: Relevance
“…In contrast, the lack of activity of the enzymes on glucose indicated that the stereo configuration of the OH-group at the carbon-4 was important for their activities. The results for the GO from the GOPS were in agreement with the reports in the literature (Whittaker, 2003;Wittaker, 2002;Mazur, 1991;Chiu et al, 1996;Sun et al, 2001;Amaral et al, 1966;Cooper et al, 1958;Avigad et al, 1962;Ettinger and Kosman, 1981). The optimum pH, temperature, thermal stability, and substrate specificity for the enzyme of the four tested isolates were similar when compared with the GO from GOPS.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the lack of activity of the enzymes on glucose indicated that the stereo configuration of the OH-group at the carbon-4 was important for their activities. The results for the GO from the GOPS were in agreement with the reports in the literature (Whittaker, 2003;Wittaker, 2002;Mazur, 1991;Chiu et al, 1996;Sun et al, 2001;Amaral et al, 1966;Cooper et al, 1958;Avigad et al, 1962;Ettinger and Kosman, 1981). The optimum pH, temperature, thermal stability, and substrate specificity for the enzyme of the four tested isolates were similar when compared with the GO from GOPS.…”
Section: Resultssupporting
confidence: 90%
“…This enzyme, which is very basic (pI = 12; Ettinger and Kosman, 1981), is reported to be inactive below pH 5.0 and to have its maximal activity at pH 6.7 -7.3 (Cooper et al, 1958;Ettinger and Kosman, 1981). This protein is reported to be stable at temperatures below 60 o C with a T 50 of 67 o C (Sun et al, 2001). Substrates for GO include dihydroxyacetone, raffinose, melibiose, lactose, guar gum, galactose, and its derivatives as galactosamine and methyl-galactopyranosides (Whittaker, 2002;Mazur, 1991;Chiu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…on May 10, 2018 by guest http://aem.asm.org/ stability and substrate specificity (9,(27)(28). To immobilize the enzyme on the surface of the PhaC protein, the protein was endowed with a coiled-coil sequence containing glutamic acid (Ecoil) or lysine residues (Kcoil), which are known to form tight heterodimers with estimated K D (equilibrium dissociation constant) values of 1 nM (6).…”
Section: Vol 76 2010 Enzyme Immobilization By Inclusion Body Displamentioning
confidence: 99%
“…The effect of temperature on peroxidase activity of wild-type and two thermostable mutants were assessed by their T 50 values ( Figure 2B) that is the temperature required to reduce the initial enzymatic activities by 50% within a given period of time and often used to quantitatively characterize thermostability. 32 The wild-type and mutants were examined by applying heat treatment for 1 h and examining the residual activity curves of the wildtype, S323Y and E328D mutants ( Figure 2B). The T 50 of S323Y and E328D mutants were 52 and 53 C, respectively, compared to 51 C for the wild-type, with the T 50 of the latter mutant slightly improved by $2 C. * These residues were not changed because RosettaDesign predicted that wild-type sequences were already optimal.…”
Section: Thermostabilitymentioning
confidence: 99%